Anisotropic thermal conductivity of the nanoparticles embedded GaSb thin film semiconductor. (21st October 2020) - Koh, Yee Rui; Lu, Hong; Gossard, Arthur C; Shakouri, Ali
Abstract: The prior theoretical model shows that GaSb is one of the few non-alloy semiconductors showing phonons ballistic effect in the thermal conductivity. However, no previous literature had been reported on the experimental measurements on the quasi-ballistic thermal transport of the GaSb thin film. In this paper, we employed the time-domain thermoreflectance (TDTR) to study the thermal transport of nanoparticles embedded GaSb thin film. Our measurements results provide first experimental evidence to verify the quasi-ballistic effect in the thermal transport of the GaSb thin film. The apparent cross-plane thermal conductivity of pure GaSb sample drops ∼15% when the pump laser modulation frequency is increased from 0.8 MHz to 10 MHz at room temperature. To further understand the thermal transport mechanism, Tempered Lévy analysis is employed to study the quasi-ballistic effect of the GaSb thin film. The model shows that GaSb thin film thermal transport has a superdiffusion exponent, α = 1.51 ± 0.23 and Lévy-Fourier transition length, r LF = 0.19 ± 0.13 µ m. Both obtained values via Tempered Lévy indicates the quasi-ballistic transport phenomena in GaSb thin film. However, this frequency dependence of the cross-plane thermal conductivity will disappear in the presence of the 3%–20% ErSb nanoparticles. Another thermal transport mechanism, i.e. anisotropic thermal transport, can be observed in GaSb thin film. The ratio of in- to cross-plane thermal conductivity varies from ∼0.2 to ∼0.7 in the 0%–20% ErSb nanoparticles volume concentrations. Detailed temperature dependence of the in-plane thermal conductivity of ErSb:GaSb samples with 0%–20% are also included in the paper for the understanding of the scattering mechanism in the thin film thermal transport. With enhanced understanding of the quasi-ballistic and anisotropic thin film thermal transport, our results might improve the thermal management efficiency of the GaSb devices.